2021
DOI: 10.4143/crt.2020.974
|View full text |Cite
|
Sign up to set email alerts
|

LASSO-Based Machine Learning Algorithm for Prediction of Lymph Node Metastasis in T1 Colorectal Cancer

Abstract: The role of tumor-infiltrating lymphocytes (TILs) in predicting lymph node metastasis (LNM) in patients with T1 colorectal cancer (CRC) remains unclear. Furthermore, clinical utility of a machine learning-based approach has not been widely studied.Materials and Methods Immunohistochemistry for TILs against CD3, CD8, and forkhead box P3 in both center and invasive margin of the tumor were performed using surgically resected T1 CRC slides. Three hundred and sixteen patients were enrolled and categorized into tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 30 publications
1
84
0
Order By: Relevance
“…Most studies report that rectal cancer patients have a statistically equal or higher rate of LNM compared with T1 CRC patients (Table 1) [6,[20][21][22][23][24][25]. Several studies presented no significant difference in the rate of LNM between colon and rectal T1 cancer patients (colon vs rectum: Oh et al, 13.1% vs 9.1%, p = 0.089; Barel et al, 6.8% vs 12.3%, p = 0.2616; Miyachi et al, 8.4% vs 11.1%, p = 0.299; and Marcias et al, 13.4% vs 16.7%, p = 0.675) [6,[23][24][25].…”
Section: Colon Vs Rectummentioning
confidence: 99%
“…Most studies report that rectal cancer patients have a statistically equal or higher rate of LNM compared with T1 CRC patients (Table 1) [6,[20][21][22][23][24][25]. Several studies presented no significant difference in the rate of LNM between colon and rectal T1 cancer patients (colon vs rectum: Oh et al, 13.1% vs 9.1%, p = 0.089; Barel et al, 6.8% vs 12.3%, p = 0.2616; Miyachi et al, 8.4% vs 11.1%, p = 0.299; and Marcias et al, 13.4% vs 16.7%, p = 0.675) [6,[23][24][25].…”
Section: Colon Vs Rectummentioning
confidence: 99%
“…No correlations were observed analyzing the CD8 positive TILs ( 21 ). Differently, a recent study by Kang et al analyzed the distribution and mean numbers of CD3, CD8, and FOXP3 positive lymphocytes in pT1 CRC and identified a significant association between lymph node metastasis and a lower number of CD8 positive lymphocytes located within the tumor core ( 49 ). In the present study, we demonstrated a correlation between absent/mild TILs and a higher risk of nodal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The LASSO regression can assist us in identifying the variables worth investigating from a huge quantity of data. 5 In this study, we explored different characteristics that may be excellent predictors for malnutrition, and we used LASSO regression to filter over 135 variables. This section of the data was then subjected to a correlation matrix analysis.…”
Section: Discussionmentioning
confidence: 99%